Effects of soil trace metals, organic carbon load and physicochemical stressors on active oxygen species metabolism in Scylla serrata sampled along the Bay of Bengal in Odisha state, India - Pati, Samar Gourav; Panda, Falguni; Jena, Srikant; Sahoo, Dipak Kumar; Paital, Biswaranjan (Frontiers in Environmental Science, 2022)
Studies on the synergetic effects of soil and water parameters on Oxidative Stress (OS) physiology systems of the edible mud crab Scylla serrata sampled from different parts of East India are unknown. This study aimed to evaluate the effects of soil Ca, Mg, and organic carbon load and water physicochemical stressors induced spatio-temporal variation of tissue-specific OS and antioxidant parameters in S. serrata along the Bay of Bengal in Odisha. Spectrophotometric or Fourier-transform infrared spectroscopy methods were employed to measure the OS physiology and physicochemical parameters. Pedological and physicochemical factors of water were varied significantly in summer (38-42 ̊C), rainy (25-35 ̊C), and winter (12-20 ̊C) seasons. Activities of antioxidant enzymes (AE) such as superoxide dismutase (SOD), catalase, glutathione peroxidase (GPx), and the level of lipid peroxidation (LPx) were found to be higher in hepatopancreas as compared to other tissues irrespective of seasonal variation. Considering the impact of dry seasons, an average of 13.23% enhanced activities of AE were noticed in different tissues of S. serrata in response to temperature, salinity, organic carbon, Mg, and Ca load of sampling sites. However, about 11.26% decrease in the activities of AEs, including GR and GST in most of the tissues were recorded, along with a 21% alleviated level of LPx observed in the rainy season compared to other seasons. Among three coastal zones of the Bay of Bengal, the AEs in crabs sampled from Chandipur were elevated by 5.43% in winter, whereas a 7.05% enhanced level of LPx was found in summer compared to crabs sampled from Chilika and Jagatsinghpur. Overall, the levels of LPx, total antioxidant, and activities of AEs (CAT, GST, GPx, and GR) have shown a positive correlation, whereas ascorbic acid and GSH negatively correlate with habitat water pH, temperature, and salinity of soil and water. The results can be used for ecotoxic and environmental biomonitoring purposes using crabs as model organisms across tropical coastal regions.